2018
DOI: 10.12669/pjms.344.14994
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of medication adherence in hypertensive patients and influential factors

Abstract: Objective:This study aims to evaluate medication adherence in hypertensive patients and to identify the influential factors.Methods:This descriptive, cross-sectional study included a total of 147 hypertensive patients who were admitted to Akdogan Health Center between December 2016 and February 2017. The Descriptive Data Form and Medication Adherence Self-Efficacy Scale were used as the data collection tools.Results:The mean Medication Adherence Self-Efficacy Scale score was found to be 70.29 ± 8.52. Age, dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
3
15
0
4
Order By: Relevance
“…Results of the multiple logistic regression analysis showed that duration of illness and number of chronic diseases were found significantly associated with medication non‐adherence. Consistent with the current study findings, Boratas & Kilic found a significant association between duration of illness and medication non‐adherence in patients with hypertension in Turkey . A study conducted by Marinho et al .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results of the multiple logistic regression analysis showed that duration of illness and number of chronic diseases were found significantly associated with medication non‐adherence. Consistent with the current study findings, Boratas & Kilic found a significant association between duration of illness and medication non‐adherence in patients with hypertension in Turkey . A study conducted by Marinho et al .…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the current study findings, Boratas & Kilic found a significant association between duration of illness and medication non-adherence in patients with hypertension in Turkey. [28] A study conducted by Marinho et al [29] has also found that increased duration of disease was associated with increased risk of non-adherence to medications in patients with type 2 diabetes in Brazil. Another study reported that longer duration of disease was a predictor of medication non-adherence in patients with diabetes in Gaza, but this association was not statistically significant.…”
Section: Discussionmentioning
confidence: 97%
“…Medication adherence is a dynamic process and can vary in individuals as well as populations, possibly increasing around clinic visits in individuals or decreasing with disease duration [ 47 , 62 ]; on the contrary, this study found that adherence to hypertension treatment improved with age and duration of diagnosis which was similar to the results of a study in Pakistan [ 63 ]. Furthermore, assessment of adherence often overestimates actual adherence, especially using a self-assessment method, as in this study with 80.4% of participants rating themselves to be adherent to treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Different factors may influence patient adherence to hypertension medications ranging from patient-related characteristics such as gender, and age, to the duration of having hypertension, and the frequency of blood pressure measurement. 8 , 9 In addition, there are other several factors of which patients’ beliefs about medication are considered an important aspect in their motivation to take the medication as prescribe. 10 Medication beliefs are thought to be more consistent in predicting adherence than demographic variables, and account for almost 20% of the variance in adherence behaviour.…”
Section: Introductionmentioning
confidence: 99%